2008
DOI: 10.1111/j.1365-3024.2008.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ‐mediated activation of enterocytes in immunological control of Encephalitozoon intestinalis infection

Abstract: The microsporidian Encephalitozoon intestinalis develops within intestinal epithelial cells (enterocytes) and is an important opportunistic diarrhoeal pathogen associated with AIDS. Little is known about the protective immune response against the parasite although in mice IFN-gamma is involved and is required to prevent dissemination of the infection to other organs. The present study was designed to establish a suitable short-term in vitro culture technique for E. intestinalis that would enable studies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Various in vitro studies have shown that the anti-parasitic actions of certain cytokines relate to their ability to induce IDO1. For example, IFNγ and TNFα have been reported to inhibit Neospora caninum (a parasite causing abortion in livestock) in human cell lines, primary cells and bovine fibroblast-like cells [492,493], Encephalitozoon intestinalis (an opportunistic diarrhoeal parasite associated with AIDS) in mouse enterocyte cells and human epithelial colorectal adenocarcinoma cells [494], Leishmania donovani (an intracellular protozoan that causes leishmaniasis) in human macrophages [441], as well as the growth of T. gondii (which can cause severe toxoplasmosis, particularly in the immunocompromised) in primary human cells and human cell lines, primarily via IDO1-mediated L-Trp starvation [441,471,[495][496][497][498][499][500]. The effectiveness of IFNγ -induced IDO1 at inhibiting T. gondii infection in vitro is, however, impaired in cells cultured under low O 2 tension [124], i.e.…”
Section: Parasitesmentioning
confidence: 99%
“…Various in vitro studies have shown that the anti-parasitic actions of certain cytokines relate to their ability to induce IDO1. For example, IFNγ and TNFα have been reported to inhibit Neospora caninum (a parasite causing abortion in livestock) in human cell lines, primary cells and bovine fibroblast-like cells [492,493], Encephalitozoon intestinalis (an opportunistic diarrhoeal parasite associated with AIDS) in mouse enterocyte cells and human epithelial colorectal adenocarcinoma cells [494], Leishmania donovani (an intracellular protozoan that causes leishmaniasis) in human macrophages [441], as well as the growth of T. gondii (which can cause severe toxoplasmosis, particularly in the immunocompromised) in primary human cells and human cell lines, primarily via IDO1-mediated L-Trp starvation [441,471,[495][496][497][498][499][500]. The effectiveness of IFNγ -induced IDO1 at inhibiting T. gondii infection in vitro is, however, impaired in cells cultured under low O 2 tension [124], i.e.…”
Section: Parasitesmentioning
confidence: 99%
“…Recently we reported that tryptophan catabolism by IDO played a key part in IFN‐γ‐mediated killing of E. intestinalis in CMT‐93 and the human enterocyte cell line Caco‐2 (Choudhry et al ., 2009). Treatment of cells with 100 U ml −1 IFN‐γ induced IDO expression and addition of 250 μg ml −1 tryptophan to cytokine‐treated CMT‐93 cells prevented IFN‐γ‐induced killing of E. intestinalis .…”
Section: Resultsmentioning
confidence: 99%
“…In our studies of IFN‐γ‐mediated killing of C. parvum by enterocyte cell lines, we found no evidence of iNOS or IDO involvement, although the expression of the enzymes themselves was not measured (Pollok et al ., 2001; Lean et al ., 2003). In contrast, we recently demonstrated that IFN‐γ inhibited development of the microsporidian Encephalitozoon intestinalis in a murine enterocyte cell line and that IDO played a key role in parasite inactivation (Choudhry et al ., 2009). This suggests that C. parvum infection of enterocytes might impair IFN‐γ‐mediated expression of IDO as a means of evading killing by the host cell.…”
Section: Introductionmentioning
confidence: 95%
“…Whereas microsporidia infect and replicate within resting macrophages, activated macrophages are currently the only cells known to be capable of killing microsporidia and contribute to immune responses via induction of inflammation and secretion of chemokines [1; 29; 30]. IFNγ plus LPS can activate macrophages to kill E. cuniculi in vitro and resistance in vivo has been demonstrated to depend on IFNγ, as well [8; 9; 10; 11; 12; 31]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to epithelial cells, E. cuniculi infects macrophages and replicates within membrane-bound parasitophorous vacuoles by inhibiting acidification to avoid fusion with lysosomes [7]. Resistance to infection has been shown to depend upon IFNγ, and macrophages can be activated by IFNγ-dependent signals to destroy the intracellular microsporidia [8; 9; 10; 11; 12; 13]. Previous in vitro studies implicated a role for reactive nitrogen species (RNS) in the process of activated macrophage-mediated killing of E. cuniculi [14; 15].…”
Section: Introductionmentioning
confidence: 99%